Agence Nationale Pour le Soutien et le Développement de L’entreprenariat en Tant Que Mécanisme de Soutien et de Développement des PME en Algérie: Étude de Cas ANSEJ Agence de Ksar Chellala - Yamani, Leila; Bensedat, Salima (جامعة طاهري محمد، بشار - كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير, 2022)
This study aimed to shed light on the National Agency for Support and Promotion of Entrepreneurship, which is one of the most important agencies designated by Algeria to promote and disseminate the entrepreneurial thought, Especially in the field of establishing small and medium enterprises, which are considered one of the entrances to economic growth. The study concluded that the National Agency for Entrepreneurship Support and Promotion has greatly contributed to the support and establishment of small and medium enterprises as a result of accompanying the idea of establishing a project until its realization through financial and moral support, and the provision of subsidies and assistance necessary for its establishment and good continuity
Keywords: التنمية المستدامة -- ريادة الأعمال -- الخدمات المصرفية -- الجزائر